(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
The dimension stone industry faces a significant environmental challenge due to the large amount of waste produced during the production process. About 51.3% of the materials extracted from dimension stone quarries worldwide end up as quarry waste. The presence of discontinuities and fractures primarily causes this waste. However, by examining the characteristics of these discontinuities and fractures and identifying in-situ blocks of the rock mass, it is possible to reduce the amount of waste produced during dimension stone quarrying. This study focuses on an abandoned quarry bench of the Lashotor quarries complex in the Isfahan Province, Iran. Due to high waste production, the quarry bench was left unused. The study aimed to identify the in-situ blocks of the quarry bench by examining the characteristics of the rock mass’s discontinuities and fractures. The authors used a modified algorithm to identify and grade all the quarry bench blocks based on the target market. The study revealed that some blocks in the abandoned quarry bench could be supplied to the target market, and the bench has the potential for block extraction. The algorithm’s modification based on the shape factor of blocks is an important innovation that increases the accuracy of block determination compared to previous methods. Overall, this algorithm can be used as a decision-making tool in extracting or not extracting the quarry bench of dimension stone quarries and implementing an optimal cutting pattern to reduce waste production.